What is the applicability of the DigComp Edu Framework for online higher education? A study with Portuguese teachers - Santos, Cassio (2024)
Introduction: To ensure that Higher Education Institutions (HEIs) can face the challenges brought about, primarily, by technological changes, it is necessary that their teaching staff prove to have adequate levels of digital competence. But what digital competence do professors need to have? Does the European Framework for the Digital Competence of Educators (DigCompEdu)) reveal to be valid for the context of higher education, in particular, in the online modality? The present study seeks to establish an answer to these questions. Method: The qualitative methodological approach was adopted and semi-structured interviews with Portuguese higher education professors was used as data collection strategy. The data were analysed through content analysis processes and presented using descriptive statistics. 22 professors who teach in online higher education participated in this study. Objective: To analyse the applicability of DigCompEdu with regard to teaching practices in the context of Online Higher Education. Results: The results indicate that DigCompEdu was considered “applicable” to online higher education, both globally and in the analysis carried out by area, ranging from “very applicable” to “applicable”. The analysis for each of the 22 competencies recorded less favourable results in competencies 6.4 “Responsible Use” and 6.5 “Problem Solving”, both contained in area 6. Discussion: The results point to the applicability of DigCompEdu in Online Higher Education